Controlabilidade exata na fronteira para o sistema de Bresse e controlabilidade exato-aproximada interna para o sistema de Bresse termoelástico - Juliano de Andrade (2017)
This work deals with boundary controllability for the Bresse system whose control acts on a part of the border. The control is obtained through the Carleman inequality and the HUM method (Hilbert Uniqueness Method) due to Lions [24] and [23]. We also studied the approximate exact control for the thermoelastic Bresse system, where the control acts in a subinterval of the domain. The control function is obtained by minimizing the functional which is associated with the thermoelasic Bresse system as done in [11]